High-intensity laser-driven secondary radiation sources using the ZEUS 45 TW laser system at the Institute of Plasma Physics and Lasers of the Hellenic Mediterranean University Research Centre. (2nd September 2021) - Clark, E. L.; Grigoriadis, A.; Petrakis, S.; Tazes, I.; Andrianaki, G.; Skoulakis, A.; Orphanos, Y.; Kaselouris, E.; Fitilis, I.; Chatzakis, J.; Bakarezos, E.; Dimitriou, V.; et al.
Abstract: The rapid development of high-intensity laser-generated particle and photon secondary sources has attracted widespread interest during the last 20 years not only due to fundamental science research but also because of the important applications of this developing technology. For instance, the generation of relativistic particle beams, betatron-type coherent X-ray radiation and high harmonic generation have attracted interest from various fields of science and technology owing to their diverse applications in biomedical, material science, energy, space, and security applications. In the field of biomedical applications in particular, laser-driven particle beams as well as laser-driven X-ray sources are a promising field of study. This article looks at the research being performed at the Institute of Plasma Physics and Lasers (IPPL) of the Hellenic Mediterranean University Research Centre. The recent installation of the ZEUS 45 TW laser system developed at IPPL offers unique opportunities for research in laser-driven particle and X-ray sources. This article provides information about the facility and describes initial experiments performed for establishing the baseline platforms for secondary plasma sources.